(untitled) (PerCursos, 2021)
In the last decades of the 19th century, the appearance of resorts on the Atlantic coast of Rio Grande do Sul favored the practice of summer retreats with therapeutic purposes prescribed by medical doctors at the time. However, this practice took on other meanings during the first decades of the 20th century, when industrialization and urbanization ruled a new way of “living in the city”. Concurrently, the planning of maritime resorts meant the projection of a social space free of urban problems, thus representing a utopia on a small scale and for a short period of time such as summer. Through the analysis of the specialized bibliography, photographs, the printed magazine A Gaivota and other sources on the coast’s history, this article shows how the beaches of Rio Grande do Sul constituted a haven of modernity between the 1920s and the 1950s, where the ideal of a better life by the ocean represented a coastal utopia in the social imagery.